Safety and glycemic outcomes of do-it-yourself AndroidAPS hybrid closed-loop system in adults with type 1 diabetes. - Andrzej Gawrecki; Dorota Zozulinska-Ziolkiewicz; Magdalena A Michalak; Anna Adamska; Michal Michalak; Urszula Frackowiak; Justyna Flotynska; Monika Pietrzak; Szymon Czapla; Bernhard Gehr; Aleksandra Araszkiewicz (PLoS ONE)
Background The aim of the study was to assess the safety and glycemic outcomes with the use of a Do-It-Yourself (DIY) Hybrid Closed-Loop (HCL) system based on the AndroidAPS application in type 1 diabetes (T1D). Methods Single-center clinical trial, with 3-week run-in and 12-week study period. DIY HCL system consisted of the Dana Diabecare RS insulin pump, Dexcom G5 continuous glucose monitoring system and AndroidAPS application. Primary outcome was safety: incidences of severe hypoglycemia, diabetic ketoacidosis, time spent in glycemia <54 mg/dl. Secondary endpoints included percentage of time in range (TIR) 70-180 mg/dl, time below 70 mg/dl, HbA1c, insulin requirements, and body weight. Results In total 12 subjects (5 men, 7 women) were enrolled, mean age 31.3±6.7, 95%CI(27.7-34.9) years, mean diabetes duration 16.1±5.7, 95%CI(13.0-19.2) years. No episodes of severe hypoglycemia or ketoacidosis were observed. Percentage of time spent in glycemia below 54mg/dl was not increased. Average sensor glycemia was lower in the study period than baseline (141.1 ± 8.4, 95%CI(136.3-145.9) vs. 153.3 ± 17.9, 95%CI(143.2-163.4), mg/dl p<0.001). TIR 70-180 mg/dl was improved by 11.3%, 95%CI(2.8%-19.8%) (from 68.0 ± 12.7 to 79.3 ± 6.4%, p<0.001), without increasing hypoglycemia time. The HbA1c level decreased by -0.5%, 95%CI(-0.9%--0.1%) (from 6.8 ± 0.5 to 6.3 ± 0.4%, p<0.001). Additionally, in the last 4 weeks of the study period participants significantly improved and showed TIR 70-180 mg/dl 82.1 ± 5.6%, 95%CI(78.9-85.3), time <54 mg/dl 0.30 (0.20-0.55)%, median 95%CI(0.1-0.7) and <70 mg/dl 1.90 (1.10-3.05)%, median 95%CI(0.7-3.2). The insulin requirement and body weight did not change in the study. Conclusions The study revealed safety of the Do-It-Yourself HCL system AndroidAPS in adults with T1D, limited to well-controlled, highly selected and closely monitored patients. The use of AndroidAPS significantly improved HbA1c, time in range and average sensor glycemia without increasing hypoglycemia. As both patients and their medical team are gaining experience using the system over time, they improve glycemic control. Trial registration German Clinical Trials Register: no. DRKS00015439; https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00015439.